Assessing the Impact of ASSURE-Based Instruction on Students’ Cognitive Ability: A Quasi-Experimental Approach - Verawati, Gita; Le, Nguyen Nhu (Schrödinger: Journal of Physics Education, 2026)
Purpose of the study: This study aims to analyze the effect of the ASSURE instructional model on students’ cognitive abilities in learning light wave concepts at the senior high school level, focusing on improving cognitive performance across Bloom’s Taxonomy levels (C1–C4). Methodology: This study employed a quasi-experimental method with a nonequivalent control group design. Data were collected using multiple-choice cognitive tests, documentation, and observation. The instrument was validated using Product Moment correlation and tested for reliability using Cronbach’s Alpha. Data were analyzed using Kolmogorov–Smirnov, Levene’s Test, and independent samples t-test. Main Findings: The results showed that the experimental group achieved higher posttest scores than the control group. The independent samples t-test indicated a significant difference (p < 0.05). The effect size analysis yielded a large effect (d = 1.34), indicating a strong impact of the ASSURE model on students’ cognitive abilities. Novelty/Originality of this study: This study provides a specific analysis of the ASSURE model’s effectiveness across cognitive levels (C1–C4) in learning light wave concepts. It also integrates learner characteristic analysis into instructional design, offering a more structured and comprehensive approach to enhancing students’ cognitive development in physics education.